THE ECONOMIC EFFECT OF THE USE OF DIFFERENT THERAPEUTIC SCHEMES IN CHILDREN WITH ACUTE INFLAMMATORY PROCESSES OF THE MAXILLOFACIAL AREA AND CHRONIC PARENCHYMAL MUMPS - Ткаченко, П.І.; Коротич, Н.М.; Лохматова, Н.М. (World of Medicine and Biology, 2014)
This article presents the results of calculating the total economic effect of the application of new scientific developments employees of Department of Pediatric Surgical Dentistry HSEE of Ukraine "Ukrainian Medical Stomatological Academy" on the complex treatment of acute purulent inflammatory diseases of the maxillofacial area in children and exacerbation of chronic parenchymatous parotitis. These integrated into everyday clinical practice in inpatient and outpatient settings will significantly reduce material costs.